Mother's Knowledge And Behavior And Family Support For Doing Baby Massage Independently At Sri Desa Clinic Gonting Malaha Kec. Bandar Pulau Kab. Asahan In 2022 - Evi Sri Maryani Pandiangan; Sukarni Setya Ningsih (International Journal of Health and Pharmaceutical (IJHP), 2023)
Mother's massage can be felt as a touch of affection which is very meaningful for the formation of the baby's personality. Through a touch of massage to the muscle tissue, blood circulation can increase to the muscle tissue or the position of the muscles can be restored and repaired, so as to improve the functions of the body's organs. Knowledge, behavior and family support greatly influence the implementation of infant massage independently. To find out the relationship between knowledge and behavior and family support for doing baby massage independently at the Sri Desa Gonting Malaha Clinic, Kec. District Island City. Asahan Year 2022. The research design is a combination of qualitative and quantitative research. The quantitative study in this study was non-experimental in nature using a cross-sectional or cross-sectional approach with the Chi-square test and taking samples using total sampling. Primary data collection was carried out using a questionnaire taking place in November 2022. Statistical test of knowledge of infant massage independently using Chi-Square with a 95% confidence interval, significance limit test α = 0.05, so the hypothesis is 0.01 <0.05. Mother's behavior towards infant massage independently with a hypothesis of 0.006 <0.0. Family support for infant massage independently, the hypothesis is 0.004 <0.05. To the clinic to provide counseling about baby massage so that every mother who participates in counseling can better understand and understand the benefits of baby massage for the growth and development of the baby.